2021
DOI: 10.1371/journal.pone.0248862
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic function impairment in children after balloon valvuloplasty for congenital aortic stenosis assessed by 2D speckle tracking echocardiography

Abstract: Aims The aim of the study was to evaluate left ventricular (LV) remodeling and systolic function using two-dimensional speckle tracking echocardiographic (2D STE) imaging in children at a long-term (more than 36 months, 107.5±57.8 months) after balloon valvuloplasty for aortic stenosis (BAV). Methods and results 40 patients (mean age 9,68 years, 75% male) after BAV and 62 control subjects matched to the age and heart rate were prospectively evaluated. The 2D STE assessment of LV longitudinal and circumferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A cut-off of 14.7% has independently been associated with the increased risk of death, underlining a potential prognostic role of GLS in asymptomatic significant AS [ 34 ]. In paediatric patients with congenital AS treated with balloon aortic valvuloplasty, post-procedural GLS was lower than in healthy children, with more impaired values in those with LV eccentric hypertrophy or with higher residual aortic gradients [ 35 ]. Carlos et al reported lower GLS values in BAV patients [ 36 ].…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…A cut-off of 14.7% has independently been associated with the increased risk of death, underlining a potential prognostic role of GLS in asymptomatic significant AS [ 34 ]. In paediatric patients with congenital AS treated with balloon aortic valvuloplasty, post-procedural GLS was lower than in healthy children, with more impaired values in those with LV eccentric hypertrophy or with higher residual aortic gradients [ 35 ]. Carlos et al reported lower GLS values in BAV patients [ 36 ].…”
Section: Diagnostic Imagingmentioning
confidence: 99%